Implementation of the parking levy policy on the side of public roads in Pangkalpinang city - Sita Arimbi; Sadu Wasistiono; Ismiyarto Ismiyarto (Sean Institute, 2024)
Based on Pangkalpinang City Regional Regulation Number 5 of 2016 concerning Public Service Levy, there are nine types of public service levy, one of which is parking levy..In terms of implementing public service levies (parking), the Pangkalpinang City government through the Pangkalpinang City Transportation Service is the driving force in implementing every policy that has been made, especially in dealing with levy issues. One of the organizations that also supports parking fees is the Regional Technical Implementation Unit (UPTD) for Transportation Technical Infrastructure Management. However pIn reality, the implementation still has many shortcomings or is still not optimal so that the targets that have been set have not yet been achieved. The theory used in this research is the theory of policy implementation from Michael Hill and Peter Hupe (2002). This theory is determined because this theory not only identifies and explains internal factors but also factors from outside the organization. The research method used in this research is qualitative. Data collection techniques in the form of interviews, observations, documentation were carried out on the side of the Pangkalpinang City public road and the Pangkalpinang City Transportation Service Office. This research was analyzed using SOAR which was used as the main strategy forimplementing the public roadside parking levy policy in Pangkalpinang City.This research describes the implementation of the parking fee policy, analyzes the inhibiting factors of the parking fee policy, and analyzes the appropriate strategy in implementing the public roadside parking fee policy in Pangkalpinang City. The findings obtained areThe implementation of the parking levy policy on the side of public roads in Pangkalpinang City has been implemented but is not yet effective. This is because some of the factors that support the successful implementation of a policy have not been fulfilled. The inhibiting factors in implementing the parking levy policy on the side of public roads in Pangkalpinang City are the attitudes and behavior of implementers, communication and external environmental factors.